Boron Dipyrromethene Nano‐Photosensitizers for Anticancer Phototherapies. Issue 32 (20th February 2019) - Sun, Wen; Zhao, Xueze; Fan, Jiangli; Du, Jianjun; Peng, Xiaojun
Abstract: As traditional phototherapy agents, boron dipyrromethene (BODIPY) photosensitizers have attracted increasing attention due to their high molar extinction coefficients, high phototherapy efficacy, and excellent photostability. After being formed into nanostructures, BODIPY‐containing nano‐photosensitizers show enhanced water solubility and biocompatibility as well as efficient tumor accumulation compared to BODIPY molecules. Hence, BODIPY nano‐photosensitizers demonstrate a promising potential for fighting cancer. This review contains three sections, classifying photodynamic therapy (PDT), photothermal therapy (PTT), and the combination of PDT and PTT based on BODIPY nano‐photosensitizers. It summarizes various BODIPY nano‐photosensitizers, which are prepared via different approaches including molecular precipitation, supramolecular interactions, and polymer encapsulation. In each section, the design strategies and working principles of these BODIPY nano‐photosensitizers are highlighted. In addition, the detailed in vitro and in vivo applications of these recently developed nano‐photosensitizers are discussed together with future challenges in this field, highlighting the potential of these promising nanoagents for new tumor phototherapies. Abstract : Boron dipyrromethene (BODIPY) nano‐photosensitizers are equipped with enhanced water solubility, biocompatibility, and tumor accumulation via the enhanced permeability and retention (EPR) effect. In addition, their excellent photostability and large molar extinction coefficient in the near infrared (NIR) region ensure a special phototherapy effect toward tumors. This review focuses on the design and preparation of BODIPY containing nano‐photosensitizers for anticancer phototherapy.